Estimating the Cost-Effectiveness of Pre-Exposure Prophylaxis to Reduce HIV-1 and HSV-2 Incidence in HIV-Serodiscordant Couples in South Africa - Jewell, Britta L. (PLoS One, 2015)
OBJECTIVE: To estimate the cost-effectiveness of daily oral tenofovir-based PrEP, with a protective effect against HSV-2 as well as HIV-1, among HIV-1 serodiscordant couples in South Africa. METHODS: We incorporated HSV-2 acquisition, transmission, and interaction with HIV-1 into a microsimulation model of heterosexual HIV-1 serodiscordant couples in South Africa, with use of PrEP for the HIV-1 uninfected partner prior to ART initiation for the HIV-1 1infected partner, and for one year thereafter. RESULTS: We estimate the cost per disability-adjusted life-year (DALY) averted for two scenarios, one in which PrEP has no effect on reducing HSV-2 acquisition, and one in which there is a 33% reduction. After a twenty-year intervention, the cost per DALY averted is estimated to be $10,383 and $9,757, respectively – a 6% reduction, given the additional benefit of reduced HSV-2 acquisition. If all couples are discordant for both HIV-1 and HSV-2, the cost per DALY averted falls to $1,445, which shows that the impact is limited by HSV-2 concordance in couples. CONCLUSION: After a 20-year PrEP intervention, the cost per DALY averted with a reduction in HSV-2 is estimated to be modestly lower than without any effect, providing an increase of health benefits in addition to HIV-1 prevention at no extra cost. The small degree of the effect is in part due to a high prevalence of HSV-2 infection in HIV-1 serodiscordant couples in South Africa.